Micromilling of biocompatible polymers (2012)
In this paper results from a research in micromachining of biocompatible polymers are presented. The paper describes the fabrication process for biocompatible polymers components and shows the accuracy levels and the dimensional scales that can be achieved with a Kern Evo micromachining center. Furthermore the paper also shows the results obtained from a microcutting test using carbide end mills of 100 microns diameter on medical-grade PMMA (Polymethyl methacrylate) specimens to determine the parameters that minimize the burrs size. To characterize the final surfaces state and the condition of the tools, optical and electronic microscopy techniques were used. The results for the first machining tests show that to control the dimensional characteristics of the component, aspects like the setting depth of cut, the selected fastening method and the alignment tolerance must be watched over; even the environmental conditions of the place where the machining center operates must be also controlled.